High-pressure structural, elastic, and thermodynamic properties of zircon-type HoPO4 and TmPO4. (20th January 2017) - Gomis, O; Lavina, B; Rodríguez-Hernández, P; Muñoz, A; Errandonea, R; Errandonea, D; Bettinelli, M
Abstract: Zircon-type holmium phosphate (HoPO4 ) and thulium phosphate (TmPO4 ) have been studied by single-crystal x-ray diffraction and ab initio calculations. We report on the influence of pressure on the crystal structure, and on the elastic and thermodynamic properties. The equation of state for both compounds is accurately determined. We have also obtained information on the polyhedral compressibility which is used to explain the anisotropic axial compressibility and the bulk compressibility. Both compounds are ductile and more resistive to volume compression than to shear deformation at all pressures. Furthermore, the elastic anisotropy is enhanced upon compression. Finally, the calculations indicate that the possible causes that make the zircon structure unstable are mechanical instabilities and the softening of a silent B 1u mode.